Media Tracking Jabar Saber Hoaks sebagai Upaya Mengendalikan Hoaks - Annisa Permata Sari; Neni Yulianita (UNISBA Press, 2023)
Abstract. The rapid development of technology and the rapid growth of internet users, especially social media in Indonesia, has made hoax information more easily spread. The spread of hoaxes will harm society and the country, the impact will be chaos in the government and the process of developing the country will be difficult. So that the government requires action in the form of controlling and monitoring existing hoaxes. This research will discuss